EFFICIENCY UTILIZATION OF GREEN TIME AT COUNTDOWN SIGNALIZED INTERSECTION - Ijeoma IHUOMA-WALTER (Journal of Construction Project Management and Innovation)
The use of countdown traffic signals, although not common in North America, is increasing in Asia and European countries. Past studies conducted albeit outside the United States have addressed some operational benefits and issues associated with the use of countdown traffic signals, including but are not limited to effect on saturation flow rate, and red light running. Experience from the successful use of pedestrian countdown signals at urban traffic intersections has engendered some local interest in the use of countdown traffic intersections has engendered some local interest in the use of countdown traffic signal devices in the United States. The purpose of this research was to analyse using driver behaviour survey the efficiency of green-time utilization rate at countdown traffic signal devices in the United States. Specifically, this research performed a comparative analysis based on the postulation that countdown traffic signal is associated with underutilized effective green time when compared to the scenario at intersections controlled by traditional (non-countdown) traffic signals. Binary regression models were developed, using data obtained from the driver behaviour survey, to estimate decision probabilities for different combinations of vehicle position (i.e. distance to the stop line) and available green time (i.e. time left before the transition to yellow phase). A comparison between the estimated decision probabilities (determined from deductive reasoning) for traditional traffic supported a pattern of underutilization of green time for the countdown signal scenario. The underutilization of green time was associated with the likelihood of drivers slowing down prematurely to stop in reaction to the visual display of available green time before the change of signal phase. Underutilization of effective green time before the change of signal phase. Underutilization of effective green time translates into a lower saturation flow rate and hence reduced intersection capacity. The findings of this research could motivate additional studies pertaining to the determination of net operational benefits or plausibility of using countdown signal devices at urban traffic intersection in the United States.